Surface property induced morphological alterations of human erythrocytes. Issue 36 (23rd July 2018) - Mukhopadhyay, Manikuntala; Ghosh, Udita Uday; Sarkar, Debasish; DasGupta, Sunando
Abstract : Retention of native erythrocyte morphology on a protein covered substrate. Abstract : Microscopic investigations of any abnormality associated with erythrocyte/red blood cell morphology constitute an important segment of the age-old peripheral smear test. Though the test is conducted on a glass slide, the effect of glass and similar other solid substrates on erythrocyte morphology remained majorly unexplored. In the first of its kind investigation, we have outlined the effect of varying the substrate surface potential on erythrocyte morphology. Such a substrate induced phenomenon has been quantified for two distinctly different drying configurations (droplets and film) upon systematically varying the cell concentration. Experimental results and supporting theoretical analysis unambiguously show the surface potential of the solid substrate to be the most influential parameter in the process of morphological alteration. The findings of the present investigation may be utilized to formulate an error-free protocol for the baseline peripheral smear test of hematological diagnosis.